Examining The Effects of Staff Retention and Engagement in the Logistics Sector - Singh, Megha; Pathak, Vipluv; Singh, Deepak; Kumar, Shresth (Journal of Neonatal Surgery, 2025)
One of the biggest issues facing the logistics industry is staff retention. Even though it plays a significant role in the global supply chain, ongoing shortages and high turnover rates indicate that more study is required in this area. In order to address this demand, this study examines the factors influencing staff retention in logistics companies. This study examines the effects of effective retention strategies and engagement practices on labor productivity, operational continuity, and customer satisfaction through a comprehensive literature review and empirical analysis. The logistics industry is unique in its challenges, which include high employee turnover, challenging work environments, and the evolving role of technology. Strong retention policies, tailored engagement efforts, and fostering a culture of gratitude and trust are all critical, as the outcomes demonstrate. Additionally, the study provides useful guidance on how logistics companies can achieve sustained success in a competitive field by balancing organizational goals with employee satisfaction. In the logistics sector, this study offers a comprehensive framework for enhancing employee experiences and strengthening organizational resilience through the integration of theoretical perspectives with practical applications. In an area crucial to global trade and business, this study contributes to the body of knowledge by addressing a substantial knowledge vacuum and offering innovative strategies for balancing employee ambitions with corporate aims.